Water Absorption Behaviour and Its Effect on the Mechanical Properties of Flax Fibre Reinforced Bioepoxy Composites - E. Muñoz; J. A. García-Manrique (International Journal of Polymer Science)
In the context of sustainable development, considerable interest is being shown in the use of natural fibres like as reinforcement in polymer composites and in the development of resins from renewable resources. This paper focuses on eco-friendly and sustainable green composites manufacturing using resin transfer moulding (RTM) process. Flax fibre reinforced bioepoxy composites at different weight fractions (40 and 55 wt%) were prepared in order to study the effect of water absorption on their mechanical properties. Water absorption test was carried out by immersion specimens in water bath at room temperature for a time duration. The process of water absorption of these composites was found to approach Fickian diffusion behavior. Diffusion coefficients and maximum water uptake values were evaluated; the results showed that both increased with an increase in fibre content. Tensile and flexural properties of water immersed specimens were evaluated and compared to dry composite specimens. The results suggest that swelling of flax fibres due to water absorption can have positive effects on mechanical properties of the composite material. The results of this study showed that RTM process could be used to manufacture natural fibre reinforced composites with good mechanical properties even for potential applications in a humid environment.